Farm Lands Brochure: Heavy Artillery In the War Between the Bulldozer and the Plow - Larissa Johnson Schneider (Journal of Applied Communications, 1982)
Thirteen months ago, the National Agricultural Lands Study (NALS) published a pamphlet to publicize its existence as a new federal agency.